APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK IDENTIFIKASI POTENSI LOKASI PAPAN IKLAN DI WILAYAH KOTA SEMARANG - Lea Kristi Agustina; Bambang Sudarsono; Andri Suprayogi (Jurnal Geodesi UNDIP, 2012)
Advertising is designed objects for the purpose of introducing, encouraging, promoting, or to draw public attention to goods, services, persons, or entities who can be seen, read, heard, felt and / or enjoyed by the public. In simple billboard interpreted as promotion tool of goods and services such as a message or information delivered through the outdoor media. The situation is quite crowded roads in Semarang City, especially in Gajah Mada, Pandanaran  and Pemuda street’s which makes existence of billboard to be one competition for providers of goods or services in order to alluring consumers in order to use the goods and services offered by them. This research aim to know the potential of billboard locations and spread along the Gajah Mada, Pandanaran and Pemuda street’s. Final results from this research provides information that can be used as review and consideration in determining the location of billboards is quite potentially, this can be done by certain agencies of local government in Semarang City and other interested parties. This research conducted by qualitative research methods which will produce descriptive data were compiled in a geographic information system to obtain map of the layout point locations spread advertisement, then performed an analysis based on the provisions of the distance between advertisement and restrictions the placement of advertisement. Based on the observation and analysis, identification potential of new billboard point locations can be done according with the specified criteria. Research results show there were 11 point of potential new billboards for the large billboard type and there are 73 point of potential new billboards to billboard medium sized types, both located on the sidewalks / curb.